High‐Efficiency Pure‐Color Inorganic Halide Perovskite Emitters for Ultrahigh‐Definition Displays: Progress for Backlighting Displays and Electrically Driven Devices. Issue 10 (14th June 2018) - Zhang, Fengjuan; Song, Jizhong; Han, Boning; Fang, Tao; Li, Jinhang; Zeng, Haibo
Abstract: All‐inorganic halide perovskites (IHPs) are ideal candidates for optoelectronic devices with outstanding emission color saturation, well‐tunable optical bandgap, near‐unity photoluminescence quantum yield (PL QY), and excellent solution processability. They appear to be promising materials for next‐generation high‐efficiency, wide‐color‐gamut, and flexible ultrahigh‐definition (UHD) displays through the backlighting in liquid‐crystal displays and electroluminescent devices. Here, the optical superiority of IHP materials for UHD displays is analyzed and summarized. In addition, recent progress regarding displays containing backlighting, and electroluminescent devices based on IHPs with different dimensions is introduced. Furthermore, a brief outlook is also provided, which identifies the current existing main problems, corresponding possible solutions, and a vision for the future. Abstract : The emerging all‐inorganic halide perovskites (IHPs) are promising materials for next‐generation ultrahigh‐definition displays, including backlighting in liquid‐crystal displays and electroluminescent devices. The optical superiority of IHP materials is analyzed. The progress in backlighting and electrically driven light‐emitting diodes based on IHPs is discussed. Conclusions and perspective, crucial for the development of IHP and display devices, are provided.